Social Interaction Patterns of Children on Special Needs (ABK) with Non-ABK Children at SDN 098166 Perumnas Pematangsiantar - Citra Adelima Saragih; Natalina Purba; Rio Parsaoran Napitupulu (International journal of technology and education research, 2026)
This study aims to describe the pattern of social interaction between children with special needs (ABK) and non-ABK children at SD Negeri 098166 Perumnas Pematangsiantar, and to identify the forms of social interaction and the inhibiting factors. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of 2 ABK children, 4 non-ABK children, and 2 class teachers. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Moleong model which includes data reduction, categorization, and data interpretation. Data validity was tested through source triangulation and technical triangulation. The results of the study indicate that social interaction between ABK and non-ABK has begun to form, but has not occurred consistently. Interactions occur more frequently during learning activities, group work, and teacher direction. The forms of social interaction found include associative interactions in the form of cooperation, mutual assistance, and social acceptance, as well as dissociative interactions in the form of passive attitudes, tendencies to be alone, and limited communication of ABK. Factors inhibiting social interaction include limited communication and low self-confidence among children with special needs, lack of understanding among children without special needs, differences in ability between students, and teacher dominance in facilitating social interaction in the classroom. Based on the research results, it can be concluded that social interaction between children with special needs and those without special needs still requires support through inclusive learning, strengthening communication skills, and the active role of teachers as social facilitators to create better and more sustainable interactions.